Approximation for Inextensible Flows of Curves in E3 - Korpinar, Talat; Turhan, Essin (Soc Paranaense Matematica, 2014)
In this paper, we construct a new method for inextensible flows of curves in E-3. Using the Frenet frame of the given curve, we present par differential equations. We give some characterizations for curvatures of a curve in E-3.
Keywords: Fluid flow; E-3; partial differential equation